1059 FAMILIAL RISK OF DILATED AND HYPERTROPHIC CARDIOMYOPATHY: A NATIONAL FAMILY STUDY IN SWEDEN. (15th December 2022) - Ricci, Fabrizio; Banihashemi, Behzad; Pirouzifard, Mirnabi; Sundquist, Jan; Sundquist, Kristina; Sutton, Richard; Fedorowski, Artur; Zoller, Bengt
Abstract: Aims: To determine the familial incidence of dilated (DCM) and hypertrophic cardiomyopathy (HCM) in first-, second- and third-degree relatives of affected individuals. Methods and results: In this population-based multigenerational cohort study, full-siblings, half-siblings, and cousin pairs born to Swedish parents between 1932 and 2015 were included and register-based DCM and HCM diagnoses among relatives were ascertained. Adjusted odds ratios (ORs) for DCM and HCM were calculated for relatives of individuals with DCM and HCM compared with relatives of individuals without DCM and HCM for reference. Total study population included 6, 334, 979 subjects and consisted of 5, 577, 449 full-siblings, 1, 321, 414 half-siblings, and 3, 952, 137 cousins. Overall, 10, 272 (0.16%) unique individuals were diagnosed with DCM and 3, 769 (0.06%) with HCM. Of these, 7, 716 (75.12%) and 2, 375 (63.01%) were males, respectively. Familial risk odds ratios (ORs) for DCM were 5.35 (95% confidence intervals (CI): 4.85-5.90) for full-siblings, 2.68 (95%CI:1.86-3.87) for half-siblings, and 1.72 (95%CI:1.12-2.64) for cousins of affected individuals. The ORs for HCM were 42.44 (95%CI:37.66-47.82) for full-siblings, 32.70 (95%CI:21.32-50.15) for half-siblings, and 36.96 (95%CI:29.50-46.31) for cousins of affected individuals. In sex-stratified analysis, relatives of affected females were found more likely to be affected than were relatives of affected males, with stronger aggregation observed for HCM. Conclusions: Familial risk of HCM and DCM is high and associated with genetic resemblance, with strongest aggregations observed in relatives of affected females with HCM, whereas this association was distinctly attenuated for DCM. The finding of a Carter effect, more pronounced in HCM, suggests a multifactorial threshold model of inheritance.